Efficacy of different bagging materials for the control of mango fruit fly (Bangladesh Journal of Agricultural Research, 2010)
Key Words: Bagging materials; control; mango fruit fly. DOI: 10.3329/bjar.v34i1.5766Bangladesh J. Agril. Res. 34(1) : 165-168, March 2009